A lipase‐catalyzed process for green synthesis of temsirolimus. Issue 2 (9th February 2015) - Ju, Xin; Li, Jianyong; Hou, Maoqi; Tao, Junhua
Abstract : Temsirolimus is an intravenous drug for the treatment of renal cell carcinoma that can be prepared using enol acyl donors, which is not favorable in process development. An improved enzymatic process to prepare temsirolimus has been developed employing lipase‐catalyzed regioselective acylation of rapamycin with environmentally friendly acyl donors. After screening of common commercial lipases and none‐enol acyl donors, it was found that p ‐nitrophenyl 2, 2, 5‐trimethyl‐1, 3‐dioxane‐5‐carboxylate reacted as efficient acyl donor when catalyzed by immobilized Thermomyces lanuginose lipase. By optimizing the process conditions (i.e., reaction temperature, solvents, and additives), the reaction time was significantly shortened while the reaction conversion reached 95.4% in methyl tert ‐butyl ether after 48 h at 50°C using the new acyl donors. This work demonstrated a cost‐effective, efficient, and scalable process to synthesize temsirolimus.